CURVA MAESTRA PARA LA CRISTALIZACIÓN DE ALEACIONES AMORFAS SB70TE30 - J. A. Rocca; M. A. Ureña; M. R. Fontana (Anales (Asociación Física Argentina), 2023)
One of the possible uses of chalcogenide glasses is their application in phase change memory devices. The operation of these non-volatile memories is based on the use of an alloy with chalcogenide elements as a sensitive material, taking advantage of the great contrast in electrical resistance between the amorphous and crystalline states. The Sb70Te30(atomic percentage) alloy stands out among the chalcogenide materials with these properties. On the other hand, the knowledge of the microscopic mechanisms of the amorphous alloys crystallization allows microstructural control to optimize properties. At this point, differential scanning calorimetry (DSC) has been widely used for the determination of the thermal stability of amorphous alloys. Previously we have started the study of the crystallization kinetics ofSb70Te30amorphous alloys. In this work, a procedure based on the so-called isokinetic hypothesis has been applied to carry out the kinetic analysis of the calorimetric data of continuous heating. In particular, the so-called master curve of the crystallization kinetics of this alloy is determined.